2022
DOI: 10.1093/ofid/ofac001
|View full text |Cite
|
Sign up to set email alerts
|

Binary Toxin Expression by Clostridioides difficile Is Associated With Worse Disease

Abstract: Background The incidence of Clostridioides difficile infection (CDI) has increased over the past two decades and is considered an urgent threat by the Centers for Disease Control. Hypervirulent strains such as ribotype 027, that possess genes for the additional toxin C. difficile binary toxin (CDT), are contributing to increased morbidity and mortality. Methods We retrospectively tested stool from 215 CDI patients for CDT by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The presence of a binary toxin locus has been associated with epidemic strains and hypervirulence of C. difficile . 44,45 CDT belongs to the family of ADP-ribosylating toxins that consist of two components: CDTa ( cdtA ), the enzymatic active ADP-ribosyltransferase which modifies cellular actin, and CDTb ( cdtB ), the binding component facilitates CDTa translocation. However, despite knowing their enzymatic activities, experimental evidence is very limited to support critical roles of CDT in C. difficile virulence.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a binary toxin locus has been associated with epidemic strains and hypervirulence of C. difficile . 44,45 CDT belongs to the family of ADP-ribosylating toxins that consist of two components: CDTa ( cdtA ), the enzymatic active ADP-ribosyltransferase which modifies cellular actin, and CDTb ( cdtB ), the binding component facilitates CDTa translocation. However, despite knowing their enzymatic activities, experimental evidence is very limited to support critical roles of CDT in C. difficile virulence.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we developed and used a strain of C difficile expressing CDTb but not CDTa to further investigate the role of CDTb during infection, and we found that expression of CDTb alone is sufficient to enhance virulence. Previous work has shown that CDT holotoxin expression has been associated with increased mortality in both humans [ 10 ] and mice [ 11 ]. In addition, although not common, clinical strains of C difficile that are negative for the primary clostridial toxins TcdA and TcdB but positive for CDT have been isolated from symptomatic patients [ 21 ], further supporting that the binary toxin CDT plays a significant role in the pathogenesis of CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is possible that the epithelial damage induced by CDTb promotes the translocation of microbes across the gut barrier, leading to bloodstream infections such as candidemia [ 24 , 25 ]. This may be another potential reason behind the increased clinical severity seen in hypervirulent strains [ 10 ], further emphasizing the need to study the effects of CDTb during infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this CDT toxin is associated with increased lethality, indicating additive pathomechanisms. Thus, the presence of the binary toxin increases the risk for severe disease progression, complications, recurrence of infection, and mortality [ 4 , 5 ]. The underlying mechanisms of hypervirulence remain unclear.…”
Section: Introductionmentioning
confidence: 99%